STATE MANAGEMENT OF THE SYSTEM OF POSTAL EDUCATION IN THE CONTEXT OF ECONOMICS KNOWLEDGE (International Journal of Innovative Technologies in Economy, 2018)
The article considers and analyzes the state management of the system of postgraduate education in the context of the "knowledge economy" that, in the global economy and the globalization of the whole society, transform into human capital in accordance with the requirements of the labor market, providing continuous training, retraining and professional development of each specialist for life. Knowledge in modern conditions becomes the main source of increased value of goods and services that determine the quality of human capital and parameters of socio-economic activity of economic entities form a qualitatively new social potential of a person - to receive and process heterogeneous information coming from different sources. Knowledge is the basis for the production and implementation of technological and managerial innovations. In addition, knowledge management solutions increase efficiency, since management is a process of using knowledge to find the most effective ways to use available information to obtain the desired results.The main characteristics of the "knowledge-based economy" are: an increase in the social product of industries directly related to the production and use of knowledge; Sustainable economic growth, based on the active use of human capital and technology, especially information and communications; intellectualization of economic activity and transformation of workers engaged in the production, transfer and use of knowledge in the dominant group in total employment; forming a single information space by creating global information networks and databases, as well as increasing the number of computer equipment; increase of immaterial accumulation and its active development in comparison with accumulation of materials; creation and development of a special type of management – knowledge management.